A cultural interpretation of the Genocide Convention - Mundorff, Kurt (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book critiques the dominant physical and biological interpretation of the Genocide Convention and argues that the idea of "culture" is central to properly understanding the crime of genocide. Using Raphael Lemkin's personal papers, archival materials from the State Department and the UN, as well as the mid-century secondary literature, it situates the convention in the longstanding debate between Enlightenment notions of universality and individualism, and Romantic notions of particularism and holism. The author conducts a thorough review of the treaty and its preparatory work to show that the drafters brought strong culturalist ideas to the debate and that Lemkin's ideas were held widely in the immediate postwar period. Reconstructing the mid-century conversation on genocide and situating it in the much broader mid-century discourse on justice and society he demonstrates that culture is not a distraction to be read out of the Genocide Convention; it is the very reason it exists"--
Outlines of a humble interpretation -- Lemkin in the cultural moment -- The Tedious crucible -- The trouble with Travaux -- A history of exclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Convention on the Prevention and Punishment of the Crime of Genocide -- (1948 December 9); Genocide (International law); Genocide -- Sociological aspects; Culture conflict; POLITICAL SCIENCE / General